The influence of maintenance therapy of rituximab on the survival of elderly patients with follicular lymphoma. A retrospective analysis from the database of the Czech Lymphoma Study Group. (October 2018) - Belada, David; Prochazka, Vit; Janikova, Andrea; Campr, Vit; Blahovcova, Petra; Pytlik, Robert; Sykorova, Alice; Klener, Pavel; Benesova, Katerina; Pirnos, Jan; Duras, Juraj; Mocikova, Heidi; et al.
Highlights: Rituximab maintenance is effective and feasible in elderly patients with FL. Induction therapy with R-CHOP is more effective than R-CVP. R-CVP + rituximab maintenance is associated with an acceptable outcome. The patients in CR + uCR had better outcomes compared to patients in PR. Abstract: The rituximab maintenance (RM) therapy for follicular lymphoma is effective and clinically well tolerated, however there is limited data regarding this from the elderly segment of the population. This analysis was performed to evaluate the efficacy of RM in elderly patients 65 years of age and older and to assess the influence of the induction therapy with immunochemotherapy (R-CHEMO) on the treatment outcome in a real world setting. A total of 232 consecutive patients treated with first-line R-CHEMO and RM (RM1 group; n = 158) or observation (RM0 group; n = 74) were analyzed. The effect of which induction therapy (R-CHOP vs. R-CVP) and the response of the patients to the first-line therapy were also evaluated. The addition of RM improved the treatment results in elderly patients. The 5- year overall survival rate in patients receiving R-CHEMO + RM1 compared to patients receiving R-CHEMO + RM0, was 83.7% (95% CI 76.1–89%) and 64.3% (95% CI 51.8–74.3%), respectively, p = 0.0012. The induction therapy with R-CHOP was found to be more effective than R-CVP but it is necessary to point out higher age of patients in the R-CVP arm. The 5- year overall survival rate in patients using R-CHOP ± RM and R-CVP ± RM was 84.9% (95% CI 77.5–90%), and 65.0% (95% CI 50.1–76.4%), respectively, p = 0.0008. The patients who achieved CR + uCR after having received first-line therapy had better outcomes compared to patients in PR. The 5- year overall survival rate in uCR + CR patients treated with R-CHEMO + RM1 and PR patients treated with R-CHEMO + RM1 was 90.6% and 68.3%, respectively, p = 0.0019. Rituximab maintenance treatment in patients 65 years and older yielded improved survival rates in a real world clinical setting. The R-CHOP regimen seems to be a more effective induction agent than R-CVP but the outcome of less intensively treated patients with R-CVP + RM is also acceptable. The achievement of uCR + CR after first-line therapy is associated with a better outcome.